Managing Regional Development In The Area of Renewable Energy Sources In Poland - Magdalena FILIPOWICZ (Communications of International Proceedings, 2024)
This article examines the challenges of power grid congestion in a municipality located in central Poland and presents potential solutions in the form of a photovoltaic farm project or prosumer group installation. In the context of growing demand for electricity and an increasing number of households producing energy from renewable sources, there is a need to upgrade the energy infrastructure to meet the needs of the local community. A planned photovoltaic farm or group prosumer installations are not only a way to relieve stressed grids, but also a step towards sustainable energy production and reduction of CO2 emissions. In the article, I also discuss the economic, social and environmental aspects of implementing these projects and the possible benefits for the municipality and its residents. My analysis indicates the potential for solar energy development in the region and presents effective tools that can help modernize energy infrastructure and promote sustainable development in local communities.
Keywords: Renewable Energy Sources; Management Of Energy Sources In The Municipality.